Planning and Development Confront in Climate Change Context - Gotame, Bharat (The Initiation, 2010)
There are ample of evidences to prove the impacts of Climate Change and will be with us for a long time to come. It will have significant impact on natural systems so that most of the habitat of living organism is directly influenced moreover the human being (which is heterotrophic in nature) and their roles to sustain the development and earth at summary are being vulnerable. This literature review article tries to summarize some climate change scenario and its increasing impact over the livelihood assets and their direct/indirect influence to development fronts. Nepal a developing country having more than 70% of mountainous regions with agriculture based economy is more susceptible to climate change impacts. Planning of development activities remarked with increasing trend of climate change impact with pivotal theme should make the development more sustainable and long living. Existing initiatives to make adaptation options are insufficient to halt the expected danger and redesigning the module of development is urgent in Nepal. On adaptation and vulnerability, a continuing effort must take place to exchange experiences and look for emerging best practices and frameworks. The urgency of the issue requires planners, policy makers, evaluators, practitioners and researchers to become involved in designing and in empowering communities and government as well. Key Words: Climate change, Development, Planning, Economic impact, Adaptation DOI: 10.3126/init.v3i0.2503 The Initiation Vol.3 2009 p.119-127